The Impact of Early Postnatal and Juvenile Social Environments on the Effects of Chronic Intranasal Oxytocin in the Prairie Vole - Prounis, George S.; Ophir, Alexander G. (Frontiers in Behavioral Neuroscience, 2019)
Interactions between social experiences at different stages of development (e.g., with parents as juveniles and peers as subadults) can profoundly shape the expression of social behavior. Rarely are the influences of more than one stage of developmental sensitivity to social environment investigated simultaneously. Furthermore, oxytocin (OT) has an extraordinary effect on a breadth of social behaviors, activationally or organizationally. The use of intranasal OT has become increasingly common therapeutically in humans and scientifically in non-human experiments, however very little attention has been paid to the potential developmental consequences on social behavior that might result. We investigated the effects of early-life social environments and the impact of chronic intranasal oxytocin on social behavior at different stages of development in male prairie voles (Microtus ochrogaster). We raised animals under two conditions: ‘socially enriched’ (in which they were biparentally reared and then weaned into group housing as subadults), or ‘socially limited’ (in which they were reared by a single-mother, and that then weaned into social isolation). Males raised under each condition were either administered daily doses of intranasal oxytocin (IN-OT) or a saline control for twenty-one days from postnatal day (PND) 21 to 42. During this time, we assessed the prosocial behavior subjects demonstrated by evaluating juvenile affiliation (as subadults), alloparental care (as adults no longer being exposed to IN-OT), and partner preference tests to assess tendencies to form adult monogamous pairbonds. We found that ‘socially limited’ males, exhibited increased social contact in juvenile affiliation tests at PND 35 and 42. These males were also more likely to form a partner preference than ‘socially enriched’ males, and formed stronger partner preferences overall. IN-OT did not alter these behavioral effects. We also found that ‘socially limited’ males exhibited a distinct response to chronic IN-OT treatment. When compared to all other treatment groups, ‘socially limited’ males that received IN-OT exhibited a greater amount of huddling behavior in the alloparental care test. This effect was, in part, explained by an absence of attack behavior, found only in these males. This study contributes to understanding the complex interactions between the developmental social environment, oxytocin, and social behavior.